Kinerja Operator Ground Support Equipment (GSE) Dalam Menjaga Keamanan Dan Keselamatan Penerbangan Di Bandar Udara Sultan Muhammad Salahuddin Bima - Subandi, Subandi; Wahyuningsih, Sri (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2025)
The aim of this research is to obtain information regarding the performance of Ground Support Equipment (GSE) Operators in Maintaining Aviation Security and Safety at Sultan Muhammad Salahuddin Bima Airport. This type of qualitative research is descriptive. There were three informants involved in this research. The results of the research showed that the Operator Performance (GSE) in providing services on the air side first carried out supervision according to the SOP, secondly monitored employee movements, unloaded cargo and facilitated mobility. So the function of GSE in this supervision includes unloading cargo and facilitating mobility. With this tool, it makes it easier for airport staff to carry out their duties. Supporting equipment used is Ground Power Unit (GPU) equipment, baggage carts, passenger ladders which are used when supervising baggage and cargo unloading. The way it works is to operate the GSE tools which are used to support the aircraft departure and arrival process.